A comparative measurement of ϕ→K+K− and ϕ→μ+μ− in In-In collisions at the CERN SPS - Arnaldi, Roberta; Banicz, K.; Castor, J.; Chaurand, B.; Chen, W.; Cicalò, C.; Colla, A.; Cortese, P.; Damjanovic, S.; David, A.; de Falco, A.; Devaux, A.; et al. (Physics letters, 2011)
The NA60 experiment at the CERN SPS has studied ϕ meson production in In-In collisions at 158 A GeV via both the K+K− and the μ+μ− decay channels. The yields and inverse slope parameters of the mT spectra observed in the two channels are compatible within errors, different from the large discrepancies seen in Pb-Pb collisions between the hadronic (NA49) and dimuon (NA50) decay channels. Possible physics implications are discussed.